DEVELOPMENT OF PRODUCTION MACHINES WITH RESPECT TO THE HUMAN FACTORS - Kotek, Luboš; Trávníček, Petr; Tůma, Zdeněk; Novotný, Lubomír (Technical university of Ostrava, 2019)
The inappropriate adaptation of the machinery to human properties and abilities may result both in physiological effects on the operator (e.g. muscle skeletal damage) resulting, for example, from inappropriate body posture, excessive or repeated exertion, and also in psycho-physiological effects such as mental overload or insuffi cient workload or stress, which may occur due to the operation, inspection or maintenance of the machine within the limits of its intended use. Psycho-physiological effects can lead to an increase in operator’s errors, lower safety or quality, thus directly affecting the quality of the production process. For these reasons, the ergonomics needs to be of high importance. The submitted paper describes the use of advanced virtual reality technologies and risk management in machine development.

The inappropriate adaptation of the machinery to human properties and abilities may result both in physiological effects on the operator (e.g. muscle skeletal damage) resulting, for example, from inappropriate body posture, excessive or repeated exertion, and also in psycho-physiological effects such as mental overload or insuffi cient workload or stress, which may occur due to the operation, inspection or maintenance of the machine within the limits of its intended use. Psycho-physiological effects can lead to an increase in operator’s errors, lower safety or quality, thus directly affecting the quality of the production process. For these reasons, the ergonomics needs to be of high importance. The submitted paper describes the use of advanced virtual reality technologies and risk management in machine development.
DEVELOPMENT OF PRODUCTION MACHINES WITH RESPECT TO THE HUMAN FACTORS
Keywords: Human factors; risk analysis; production machines; Human factors; risk analysis; production machines